Statistical issues in epidemiological studies of gene-environment interaction - Kraft, Peter; Spiegelman, Donna (Henry Stewart Talks, 2007)
Gene-environment interaction in the development of human traits, including disease, Conceptual and analytical challenges, Joint analysis of data on both genetic and environmental factors from epidemiologic studies as a way to increase power to detect a polymorphism (or an exposure) that is associated with disease risk, Study designs, Statistical modeling issues in the analysis of data, Sample size and power calculations for a range of designs, Specification of parameters, Ordinal coding, Hierarchical models, The analysis of highdimensional "pathway" data (multiple related genes and environmental exposures)